EFFECT OF TOTAL PHENOLIC AND TOTAL FLAVONOID LEVELS ON THE ANTIOXIDANT POWER OF WATER EXTRACT, ETHANOL AND CHLOROFORM OF GREEN TEA LEAVES (Camellia sinensis L) - Ahwan Ahwan; Anik Suwarni; Reni Ariastuti; Rosyadah Hafidz; Sinta Mei Enjelina (Sekolah Tinggi Farmasi Muhammadiyah Cirebon, 2024)
Tea (Camellia sinensis L.) was originally used as a refresh drink. Tea has many benefits, especially for health and beauty. The most widely used tea in the market is green tea, because its properties can be used as a daily drink to improve the quality of life in carrying out daily activities. The aim of this study was to determine the effect of the relationship between total phenolic and total flavonoid levels in water extract (EA), ethanol (EE), and chlorophorom (EK) of green tea leaves on antioxidant power. This experimental study used the extraction method, qualitative analysis, quantitative analysis using the colorimetric method, and antioxidant power using the DPPH method. The data obtained were statistically analyzed using SPPS and Microsoft Excel. The results obtained in The extraction process yielded extracts: EA (21.44%), EE (11.20 %), and EK (3.58 %). Qualitative analysis of flavonoid and phenolic compounds in all the extracts revealed the presence of these compounds. In the total phenolic test, the levels were: 229.07 ± 0.99 (EA); 573.70 ± 3.93 (EE); 45.27 ± 0.73 mg/g (EK) GAE (Galic Acid Equivalent). Meanwhile, the flavonoid content was 13.10 ± 0.31 (EA); 40.49 ± 0.67 (EE); 20.94 ± 0.50 mg/g (EK) QE (Quercetin Equivalent). The antioxidant results have an IC50 (Inhibitory Concentration) value of 34.64 ± 0.74 (EA); 7.02 ± 0.15 (EE); 99.11 ± 1.23; positive control 5.94 ± 0.07 µg/mL (vitamin C) ...